Image-Guided Biopsy and Treatment of Musculoskeletal Tumors - Hillen, Travis J.; Baker, Jonathan C.; Jennings, Jack W.; Wessell, Daniel E. (Seminars in Musculoskeletal Radiology, 2013)
This article reviews the basics of image-guided intervention of musculoskeletal neoplasms. Image-guided procedures are playing an ever-increasing role in the diagnosis, staging, and treatment of musculoskeletal tumors. The successful handling of these lesions necessitates a multidisciplinary approach, with the radiologist working closely with the orthopedic oncologic surgeon, medical oncologist, radiation oncologist, and pathologist to ensure that the procedure is performed in a way that maximizes the chance of definitive diagnosis and/or the treatment effect while minimizing potential complications. To accomplish these goals, the radiologist must be familiar with the indications and contraindications for any biopsy or treatment, effective procedure planning (e.g., selection of biopsy path, type of imaging guidance and biopsy needle, etc.), proper specimen handling, and potential treatment options such as thermal ablation or cement augmentation. Continued involvement after the procedure—including follow-up to ensure that pathology is concordant with imaging—is also crucial.
Keywords: biopsy; sarcoma; metastasis; radiofrequency ablation; cryoablation